2013
DOI: 10.1037/h0099207
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sex-typical body shape and quality indicators.

Abstract: Sex-typical body shapes (a man's muscular physique and a woman's hourglass figure) are an outcome of evolutionary adaptation in reproductive fitness because they convey information about gene quality, health and fertility, which are important elements for mate selection. Therefore, sex-typical body shape should be linked to other known physical attributes related to reproductive success. The purpose of this study was to investigate the relationships between sex-typical body shape and morphological traits that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 117 publications
1
6
0
2
Order By: Relevance
“…Thus, SHR represents an informative anthropomorphic measurement of male upper-body configuration. As predicted, HGS has been shown to be positively correlated with SHR in all samples, including one with female participants ( Gallup et al, 2007 , 2010 ; Sim, 2013 ).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, SHR represents an informative anthropomorphic measurement of male upper-body configuration. As predicted, HGS has been shown to be positively correlated with SHR in all samples, including one with female participants ( Gallup et al, 2007 , 2010 ; Sim, 2013 ).…”
Section: Introductionsupporting
confidence: 76%
“…Studies examining the connection between HGS and fluctuating asymmetry (FA) – a measure of developmental stability and health – provide much more inconsistent results. The first study to investigate this relationship measured six bilateral traits, and found that HGS was negatively correlated with FA in women but not men ( Sim, 2013 ). Combining measurements across 12 paired traits, HGS was found to be negatively correlated with FA within a subsequent sample of men ( Fink et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Van Dongen and Gangestad [257] and Van Dongen [256] conducted meta-analyses of published papers and concluded that the literature did not support an association between facial symmetry and attractiveness. Moreover, a second meta-analysis by Van Dongen [258] failed to find an association between developmental instability, as measured by fluctuating asymmetry, and perceived masculinity or femininity (but see [259]). Finally, an additional study by Van Dongen [260] also failed to find an association between attractiveness and facial symmetry.…”
Section: Evolutionary Biologymentioning
confidence: 99%
“…It has been shown that in males SHR is correlated with such masculine traits as hand-grip strength [ 40 ] and sexual behaviour (e.g. age at first sexual intercourse or number of sex partners [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%